The Development of Schenker's Concept of Interruption. (23rd July 2013) - Marston, Nicholas
Abstract This article draws on the rich resources of Heinrich Schenker's Nachlass in the Ernst Oster Collection (New York Public Library) to construct the development of interruption (Unterbrechung), a vital aspect of Schenker's mature understanding of musical form. In §90 of Der freie Satz (1935) Schenker makes a crucial distinction between the structural weight of the two <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg3jzbz0cr" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /></alternatives> configurations in an interrupted <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg3jzbz0b6" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /></alternatives>Ursatz, and gives priority to the first one: the effect of interruption depends on the sense that this will be succeeded by <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg3jzbz0k2" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /></alternatives>, rather than by the return to <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg3jzbz0jh" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /></alternatives> that is actually forthcoming. Subsequently, in §93, Schenker claims that the reasserted <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg3jzbz0hz" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /></alternatives> connects back to its first appearance, prior to the first arrival of <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg3jzbz0gd" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /></alternatives>. The article explores the tension between these two claims in relation to <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg3jzbxzpq" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /></alternatives> and <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg3jzbxzq8" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /></alternatives>Ursätze and reconstructs preliminary versions of the text relating to interruption in Der freie Satz. It concludes by suggesting that Schenker's shifting notation of interrupted structures reflects a continuing uneasiness with his own definition of interruption as a theoretical concept.